Regional Institutional Arenas for Social Innovation: A Mixed Methods Research - Chatzichristos, Georgios; Nagopoulos, Nikolaos (Journal of Social Entrepreneurship, 2021)
Social innovation is conceptualised as having two intimately related pillars: institutional innovation and locally embedded innovation, in the sense of social economy. Two main research questions were addressed: how political, institutional innovation is fostered and how does it influence social economy? A mixed methods research was conducted in the Mühlviertel NUTS3 region. Despite a framework of enhanced autonomy and institutional innovation for the main stakeholders, both macro and micro analysis illustrate a lack of intermediate space to: a) link the innovative agenda to high-state political agendas, and b) link institutional innovation to social economy.
Keywords: Innovation sociale; Méthodes; Réservé UdeM

Regional Institutional Arenas for Social Innovation: A Mixed Methods Research - Chatzichristos, Georgios; Nagopoulos, Nikolaos (Journal of Social Entrepreneurship, 2021)
Social innovation is conceptualised as having two intimately related pillars: institutional innovation and locally embedded innovation, in the sense of social economy. Two main research questions were addressed: how political, institutional innovation is fostered and how does it influence social economy? A mixed methods research was conducted in the Mühlviertel NUTS3 region. Despite a framework of enhanced autonomy and institutional innovation for the main stakeholders, both macro and micro analysis illustrate a lack of intermediate space to: a) link the innovative agenda to high-state political agendas, and b) link institutional innovation to social economy.
Keywords: Innovation sociale; Méthodes; Réservé UdeM